2022
DOI: 10.51505/ijebmr.2022.6304
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands-job Resources and Organizational Trust: Mediation Role of Employee Engagement, Psychological Well-being, and Transformational Leadership

Primari Puteri Widanti,
Sinto Sunaryo

Abstract: This study aims to determine the relationship of job demands and job resources with organizational trust through employee engagement, psychological well-being, and transformational leadership. This study involved 235 participants from Dr. Moewardi Regional Public Hospital and Universitas Sebelas Maret Hospital in Surakarta, uses a quantitative approach with convenience sampling technique by considering the risk level of being exposed to COVID-19. Data is collected by an online survey using google form question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…A review study carried out by Tongtong and Yusuf [ 59 ] revealed that TLS plays a significant contribution in enhancing the PWB of subordinates. Further, a highly significant correlation between TLS and PWB (β = 0.687, p < 0.001) was mentioned by Widanti and Sunaryo [ 60 ] in their study of a sample of 235 participants in some of Surakarta’s hospitals (Indonesia). Moreover, in the hotel industry setting, Kloutsiniotis et al [ 61 ] illustrate that TSL plays a vital role in reducing stress, anxiety, and workplace loneliness caused by COVID-19 and eliminates the adverse impacts of stressors on hotel staff burnout.…”
Section: An Overview Of the Theoretical Background And The Developmen...mentioning
confidence: 89%
“…A review study carried out by Tongtong and Yusuf [ 59 ] revealed that TLS plays a significant contribution in enhancing the PWB of subordinates. Further, a highly significant correlation between TLS and PWB (β = 0.687, p < 0.001) was mentioned by Widanti and Sunaryo [ 60 ] in their study of a sample of 235 participants in some of Surakarta’s hospitals (Indonesia). Moreover, in the hotel industry setting, Kloutsiniotis et al [ 61 ] illustrate that TSL plays a vital role in reducing stress, anxiety, and workplace loneliness caused by COVID-19 and eliminates the adverse impacts of stressors on hotel staff burnout.…”
Section: An Overview Of the Theoretical Background And The Developmen...mentioning
confidence: 89%